1988
DOI: 10.1161/01.atv.8.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-type plasminogen activator antigen and plasminogen activator inhibitor in diabetes mellitus.

Abstract: Parameters of flbrlnolysls, Including euglobulln fibrlnolytlc activity, tissue-type plasminogen activator (t-PA) antigen, plasminogen activator Inhibitor (PA-lnhlbltor) activity, and plasmln-aj-antlplasmln complex (PAP) were studied In 62 patients (35 women and 27 men; ages 53 ± 16 years) with either Insulin-dependent (IDDM) or nonlnsulln-dependent (NIDDM) diabetes mellKus. Compared to a control group of similar age (n = 57), the diabetic patients had a significantly lower mean euglobulln fibrlnolytlc activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
118
0
3

Year Published

1991
1991
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(135 citation statements)
references
References 19 publications
14
118
0
3
Order By: Relevance
“…Although the AGE effects appeared to be modest, we speculate that chronic exposure to AGE during prolonged hyperglycaemia causes blood vessels to become more susceptible to fibrin formation and stabilization. Actually, a decrease of approximately 30 % in plasma PGI 2 was a risk factor for diabetic vascular complications [38], and about a one and one halffold increase in plasma PAI-1 activity resulted in an impaired fibrinolytic capacity in various thrombogenic disorders [6,8,10]. In addition, a synergistic involvement of glucose and AGE on reduced fibrinolysis was suggested by Maiello et al [39] who showed that high glucose increased the PAI-1 activity in HU-VEC by approximately 120 %.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the AGE effects appeared to be modest, we speculate that chronic exposure to AGE during prolonged hyperglycaemia causes blood vessels to become more susceptible to fibrin formation and stabilization. Actually, a decrease of approximately 30 % in plasma PGI 2 was a risk factor for diabetic vascular complications [38], and about a one and one halffold increase in plasma PAI-1 activity resulted in an impaired fibrinolytic capacity in various thrombogenic disorders [6,8,10]. In addition, a synergistic involvement of glucose and AGE on reduced fibrinolysis was suggested by Maiello et al [39] who showed that high glucose increased the PAI-1 activity in HU-VEC by approximately 120 %.…”
Section: Discussionmentioning
confidence: 98%
“…Although epidemiological studies have established the plasma PAI-1 elevation in diabetes [9,10], there is no clinical evidence suggesting plasma AGE concentrations as a major contributor to the PAI-1 concentration. Further studies would be required to determine a cause-to-effect relationship between AGE and PAI-1 in diabetic patients, including intervention studies with AGE inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Alterations in PAI-1 and other gene products merit further investigation as drug-eluting stents are applied more broadly as the antiproliferative and prothrombotic effects may be magnified or diminished in other vascular beds or in patients that constitutively overproduce PAI-1, such as Type 2 diabetics or patients with the metabolic syndrome. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Although PAI-1 concentrations are elevated in the plasma of Type 2 diabetic patients [22,23], the effects of Type 1 diabetes mellitus on plasma PAI-1 levels are controversial. Some reports indicate that plasma PAI-1 levels are increased in Type 1 diabetic patients [24][25][26][27], whereas others indicate normal levels [22,[28][29][30]. However, the molecular mechanism of diabetes-induced PAI-1 expression has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%